1998
DOI: 10.1021/om980722n
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Complexes of Group 4 Metals Containing a Tridentate-Linked Amido−Cyclopentadienyl Ligand:  Synthesis, Structure, and Reactivity Including Ethylene Polymerization Catalysis

Abstract: A series of group 4 metal complexes M(η5:η1:η1-C5Me4SiMe2NCH2CH2X)R2 (M = Ti; R = Me, CH2Ph; M = Zr, Hf; R = Me, Et, nPr, nBu, CH2Ph, CH2SiMe3, Ph) containing the tridentate-linked amido−tetramethylcyclopentadienyl ligand C5Me4SiMe2NCH2CH2X (X = OMe, NMe2) were synthesized by alkylation of the dichloro complexes M(η5:η1:η1-C5Me4SiMe2NCH2CH2X)Cl2. The complexes were characterized by 1H and 13C NMR spectroscopy, mass spectrometry, and elemental analysis. Nuclear Overhauser effect measurements of the dimethyl com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 92 publications
5
45
0
Order By: Relevance
“…These bond distances are similar to those reported in the literature. The Zr-C aryl bond distance is 2.298(3) Å , which is consistent with other Zr-phenyl complexes [35]. The two iodides in the axial positions have Zr-I bond lengths of 2.8087(5) and 2.8160(5) Å .…”
Section: Preparation Characterization and Molecular Structure Of 2-(supporting
confidence: 86%
“…These bond distances are similar to those reported in the literature. The Zr-C aryl bond distance is 2.298(3) Å , which is consistent with other Zr-phenyl complexes [35]. The two iodides in the axial positions have Zr-I bond lengths of 2.8087(5) and 2.8160(5) Å .…”
Section: Preparation Characterization and Molecular Structure Of 2-(supporting
confidence: 86%
“…The structure found for complex 24 (Scheme 10) [25] confirmed that the zirconium centre shows a profoundly distorted trigonal bipyramidal coordination in which the equatorial plane is defined by the iminoacyl and the two silylamido nitrogen atoms and the apical positions are occupied by the cyclopentadienyl ring and the iminoacyl carbon atom in contrast to the pseudo-square-pyramidal coordination [29] found for the mono-insertion product in singly bridged compounds. Double insertion in the dialkyl derivative [Zr{g 5 -C 5 Me 4 (SiMe 2 -g-NtBu)}Me 2 ] afforded a pseudo-octahedral configuration [30] in which, one atom of the iminoacyl groups occupies the axial or the equatorial position, depending on the R substituent of the isocyanide.…”
Section: Insertion Reactionsmentioning
confidence: 66%
“…Overall yield from 5 was 75%. The NMR data for the bis(dimethylamido)titanium complex: 1 H NMR (C 6 D 6 ): d 0.99 (dd, 3 J HH = 6.8 Hz, (16) 17.172 (6) 15.373(7) c (Å ) 16.261 (17) 14.795 (5) 17.746(7) a (°) 9 0 9 0 9 0 b (°) 90 103.857 (11) 98.110(14) c (°) 9 0 9 0 9 0 V (Å 3 ) 2440 (4) …”
Section: Compound 11mentioning
confidence: 99%
“…Additional coordination of phosphorous might be attributed to the low activity[16]. Very low activities compared with the standard CGC were observed with the dimethylsilyleneFig.…”
mentioning
confidence: 96%